AN OPEN ACCESS SCHOLARLY ENCYCLOPEDIA FOR MUSIC: A CALL TO ACTION - Shirts, Peter (Notes (Music Library Association), 2021)
While the idea of reference sources has become synonymous with the internet, online scholarly encyclopedias in music are currently only accessible to those affiliated with institutions that can afford expensive annual subscriptions and to those individuals who purchase costly personal subscriptions. Meanwhile, backup print copies have been inaccessible in libraries closed for the COVID-19 pandemic or closed to unaffiliated visitors. An open access scholarly music encyclopedia could solve these access problems while increasing the visibility and relevance of music scholarship and expanding the possible modes of digital analysis. This paper considers existing models of open access and identifies some potential paths forward for an open access scholarly subject encyclopedia, including leveraging Wikipedia, creating a new encyclopedia, or lobbying publishers to convert existing music encyclopedias to open access using a "subscribe to open" funding model.